ENT 530 Social Media Portfolio: Faris Photographic Engraving / Faris Luqman Marzuki - Marzuki, Faris Luqman (2021)
‘Faris Photographic Engraving’ is a local company that makes engraving images from Mukim Telaga Mas, Kedah, Malaysia. It was discovered by me and my father, my father who had the idea to venture into the field of photoengraving because it is becoming increasingly popular among the current generation. My father got the idea for this business after visiting a custom frame manufacturing factory. My father noticed a CNC laser machine engraving the frame in the factory. This piqued my father's interest in purchasing a laser machine from China, as a result of multiple experiments he had conducted to understand how to use, effect, and rate of capabilities. He was very interested in making picture carvings on wood and acrylic materials, but he was unable to do so due to a lack of understanding of the proper techniques. After finishing my diploma, I focused on understanding and conduct various experiments in order to understand how to operate the machine. Finally, in May 2020, I completed a picture carving on a wooden surface and received several customer orders. I don't have a social media account to promote my services because I don't know how to set up a business page. I opened an official Facebook account for my business after receiving advice from my lecturer, Dr. Muhammad Iskandar Hamzah, and I now have 38 followers. In the future, I plan to open another Instagram account in the hopes of attracting customers to use my services.